(+)-Spectaline and iso-6-spectaline induce a possible cross-talk between autophagy and apoptosis in Trypanosoma brucei rhodesiense - Lim, Kah Tee; Yeoh, Chiann Ying; Zainuddin, Zafarina; Adenan, Mohd Ilham (MDPI, 2019)
In our previous study, two known piperidine alkaloids (+)-spectaline (1) and iso-6-spectaline (2) were isolated from the leaves of Senna spectabilis and showed no toxic effect on L6 cells. In view of the potential use of piperidine alkaloids in S. spectabilis for the treatment of sleeping sickness, further investigation on the cell death actions of the parasite after treatment with compound 1 and 2 suggested that the treated parasites died by a process of autophagy based on the characteristic morphological alterations observed in intracellular T. b. rhodesiense. In search for apoptosis, interestingly, trypanosomes treated with high concentration of compound 1 and 2 after 72 h significantly induced an early apoptosis-like programmed cell death (PCD) such as phosphatidylserine (PS) exposure, loss of mitochondrial membrane potential and caspases activation. No DNA laddering discriminated late apoptosis event. Taken together, these findings demonstrated the potential of compound 1 and 2 as a natural chemotherapeutic capable of inducing a possible cross-talk between autophagy and apoptosis in T. b. rhodesiense.